Noradrenergic modulation of activity in a vocal control nucleus in vitro - Solis, Michele M. (2005)
Norepinephrine (NE) can profoundly modulate sensory processing, but its effect on motor function is less well understood. Birdsong is a learned behavior involving sensory and motor processes that are influenced by NE. A potential site of NE action is the robust nucleus of the arcopallium (RA): RA receives noradrenergic inputs and has adrenergic receptors, and it is a sensorimotor area instrumental to song production. We hypothesized that NE modulates RA neurons, and as a first test, we examined the effect of NE on RA activity in vitro. We recorded spontaneous activity extracellularly from isolated RA neurons in brain slices made from adult male zebra finches. These neurons exhibited regular tonic activity with firing rates averaging 5.5 Hz. Bath application of NE rapidly and reversibly decreased firing for the majority of neurons, to the extent that spontaneous activity was often abolished. This was likely a direct effect on the cell recorded, since it occurred with blockade of fast excitatory and inhibitory synaptic transmission, or of all synaptic transmission. The NE-induced suppression involved the α2-adrenergic receptor: yohimbine, an antagonist, completely reversed the suppression, and clonidine, an agonist, partially mimicked it. Perforated patch recordings revealed that NE induced a conductance increase in RA neurons; however, this did not prevent cells from firing when stimulated by afferents in HVC. For some neurons, NE application resulted in an increase in signal-to-noise ratio for spikes evoked by HVC stimulation. Thus, NE could strongly modulate the spontaneous activity of RA cells, potentially enhancing signals relayed through RA.